Assessment of Inhibin-B hormone level and its relationship with some gonadal hormones in males having idiopathic infertility - Fakhry Gazal Mohammad; Adnan F. AL-Azzawie (Tikrit Journal of Pure Science, 2022)
The aim of the current study to determine levels of Inhibin-B hormone and its relationship with some gonadal hormones, including follicle-stimulating hormone (FSH), luteinizing hormone (LH) prolactin, and testosterone hormones in some males with idiopathic infertility in Shirqat city.